Chemical synthesis of disulfide surrogate peptides by using beta-carbon dimethyl modified diaminodiacids. Issue 41 (6th October 2021) - Cui, Ji-Bin; Wei, Xiao-Xiong; Zhao, Rui; Zhu, Huixia; Shi, Jing; Bierer, Donald; Li, Yi-Ming
Abstract : We report the first example of thioether bridged diaminodiacids incorporating Cys Cβ dimethyl modification. Abstract : The replacement of disulfide bridges with metabolically stable isosteres is a promising strategy to improve the stability of disulfide-rich polypeptides towards reducing agents and isomerases. A diaminodiacid-based strategy is one of the most effective methods to construct disulfide bond mimics, but modified diaminodiacids have not been developed till now. Inspired by the fact that alkylation of disulfide bonds can regulate the activity of polypeptides, herein, we report the first example of thioether bridged diaminodiacids incorporating Cys Cβ dimethyl modification, obtained by penicillamine (Pen)-based thiol alkylation. The utility of these new diaminodiacids was demonstrated by the synthesis of disulfide surrogates of oxytocin containing a short-span disulfide bond and of KIIIA with large-span disulfide bonds. This new type of synthetic bridge further extends the diaminodiacid toolbox to facilitate the study of the structure–activity relationship of disulfide-rich peptides.